Proposed new design of Tiny Tapir retail at Lot 13, Jalan Telawi 3, 59100 Wilayah Persekutuan Kuala Lumpur / Nur Shazrina Abdul Majid - Abdul Majid, Nur Shazrina (2010)
Retail comes from the French word retainer, which refers to "cutting off, clip and divide" in terms of tailoring (1365). It first was recorded as a noun with the meaning of a "sale in small quantities" in 1433 (French). Its literal meaning for retail was to "cut off, shred, paring". Like the French, the word retail in both Dutch and German (detailhandel and Einzelhandel respectively), also refers to the sale of small quantities of items. Retailing consists of the sale of goods or merchandise from a very fixed location, such as a department store, boutique or kiosk, or by mail, in small or individual lots for direct consumption by the purchaser. Retailing may include subordinated services, such as delivery. Purchasers may be individuals or businesses. In commerce, a "retailer" buys goods or products in large quantities from manufacturers or importers, either directly or through a wholesaler, and then sells smaller quantities to the end-user. Retail establishments are often called shops or stores. Retailers are at the end of the supply chain. Manufacturing marketers see the process of retailing as a necessary part of their overall distribution strategy. The term "retailer" is also applied where a service provider services the needs of a large number of individuals, such as a public utility, like electric power. Shops may be on residential streets, shopping streets with few or no houses or in a shopping mall. Shopping streets may be for pedestrians only. Sometimes a shopping street has a partial or full roof to protect customers from precipitation. Online retailing, a type of electronic commerce used for business-to-consumer (B2C) transactions and mail order, are forms of non-shop retailing. Shopping generally refers to the act of buying products. Sometimes this is done to obtain necessities such as food and clothing; sometimes it is done as a recreational activity. Recreational shopping often involves window shopping and browsing and does not always result in a purchase.